Indicators of Sustainable Development of the Province of Warmia and Mazury in the Environmental Aspect - Witkowska-Dąbrowska, Mirosława (Olsztyn Economic Journal, 2016)
The purpose of this study has been to identify the degree of sustainability in the development of the Province of Warmia and Mazury. The theoretical and empirical investigations were conducted between 2003-2014 based on data from the Local Data Bank. Using a comparative indicator method, 20 indicators were developed, with different directions of preference. The evaluation involves the concept of uniform preference, hence the higher the assessment indicator, the better the situation in the evaluated area unit. Our studies on the sustainable development of the Province of Warmia and Mazury suggest that the indicators measuring the environmental dimension and consequently the quality of life of the residents (in this aspect) score higher than the country's average values. It is also optimistic that some progress, however small, can be seen in this area based on the analyzed dynamics of changes.